2019
DOI: 10.1159/000502523
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury and Long-Term Risk for Cardiovascular Events in Patients after Kidney Transplantation

Abstract: Background: Acute kidney injury (AKI) was found to be associated with an increased risk of major adverse cardiovascular events (MACE) in the general population. Patients after kidney transplantation are prone to AKI events and are also at an increased risk of cardiovascular (CV) disease. The association between AKI and MACE in kidney transplant patients is yet to be studied. Methods: This retrospective single-center cohort study reviewed 416 adult renal allograft recipients transplanted between 2005 and 2010. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…104 In retrospective studies of RTRs and LTRs from both living and deceased donors, acute kidney injury (AKI) was associated with increased rates of major adverse CV events, CV mortality, and all-cause mortality. 105,106 In a study of short-term MACE within 30 d of LT, hepatorenal syndrome was found to be an independent predictor for MACE. 107 Among hospitalized patients with AKI stratified by resultant renal recovery, those with complete recovery had a 23% risk reduction for long-term CV events.…”
Section: Management Strategies For Post-lt Htn: Lifestyle Modificatio...mentioning
confidence: 99%
“…104 In retrospective studies of RTRs and LTRs from both living and deceased donors, acute kidney injury (AKI) was associated with increased rates of major adverse CV events, CV mortality, and all-cause mortality. 105,106 In a study of short-term MACE within 30 d of LT, hepatorenal syndrome was found to be an independent predictor for MACE. 107 Among hospitalized patients with AKI stratified by resultant renal recovery, those with complete recovery had a 23% risk reduction for long-term CV events.…”
Section: Management Strategies For Post-lt Htn: Lifestyle Modificatio...mentioning
confidence: 99%
“…KTRs with AKI showed an increased risk of cardiovascular disease and mortality with respect to KTRs without AKI. A recent retrospective, single-center cohort study reported that AKI is associated with a 38% increased risk of major adverse cardiovascular events (MACE) and an 86% increased risk of cardiovascular mortality [129]. However, preexisting cardiovascular diseases before kidney transplantation may represent a risk factor for ICU admission and mortality rate among this population.…”
Section: Graft and Patients' Outcomesmentioning
confidence: 99%
“…AKI progression to chronic kidney disease (CKD) in KTRs occurred in roughly half of ICU survivors at 6 months with hospital and 6-month mortality rates of 20% and 26.5%, respectively [8]. Independent of AKI, cardiovascular disease and development of donor-specific antibodies in the ICU may negatively impact graft survival [8,9]. De novo donor-specific antibody (DSA) can form after transfusions and reduction of immunosuppression.…”
Section: Introductionmentioning
confidence: 99%